An experimental evaluation of selective mutation - Offutt, A.J.; Rothermel, G.; Zapf, C. (Proceedings of 1993 15th International Conference on Software Engineering, 1993)
Mutation testing is a technique for unit-testing software that, although powerful, is computationally expensive. The principal expense of mutation is that many variants of the test program, called mutants, must be repeatedly executed. Selective mutation is a way to approximate mutation testing that saves execution by reducing the number of mutants that must be executed. The authors report experimental results that compare selective mutation testing to standard, or nonselective, mutation testing. The results support the hypothesis that selective mutation is almost as strong as nonselective mutation. In experimental trials, selective mutations provide almost the same coverage as nonselective mutation, with significant reductions in cost.< >